2016
DOI: 10.1016/j.gfs.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Horticultural exports and food security in developing countries

Abstract: This article reviews the channels through which horticultural exports affect food security in developing countries. We describe the trends in horticultural export chains and investigate the macro-and micro-level effects on the different components of food security, including availability, access, utilization and stability. The available evidence suggests that horticultural exports contribute to food security in developing countries, particularly through the development of rural labor markets and female wage em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 93 publications
(97 reference statements)
1
28
0
3
Order By: Relevance
“…She concluded that diversification towards high‐value crop production was taken up by poor farming households as a survival strategy in places where lack of publicly supplied irrigation made it impossible to survive on water‐intensive traditional crops and that poor and marginal farmers found it very hard to avoid extreme poverty and malnutrition by taking resort to diversification. According to Van den Broeck and Maertens (), the evidence available suggests that at the macro‐level, the production of high‐value crops for the export market can contribute to the stability of food security in developing countries and does not necessarily reduce food production for the country domestic market. However, these authors highlight the scarcity of empirical evidence at the macroeconomic level that directly measures the implications of increased horticultural exports for food availability and access.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…She concluded that diversification towards high‐value crop production was taken up by poor farming households as a survival strategy in places where lack of publicly supplied irrigation made it impossible to survive on water‐intensive traditional crops and that poor and marginal farmers found it very hard to avoid extreme poverty and malnutrition by taking resort to diversification. According to Van den Broeck and Maertens (), the evidence available suggests that at the macro‐level, the production of high‐value crops for the export market can contribute to the stability of food security in developing countries and does not necessarily reduce food production for the country domestic market. However, these authors highlight the scarcity of empirical evidence at the macroeconomic level that directly measures the implications of increased horticultural exports for food availability and access.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the participation of women in high‐value crop production for the export markets, Dolan and Sorby () found no indication that household nutritional and health status was negatively affected, and Van den Broeck and Maertens () observed that the development of rural labour markets and participation of women was favourable to improved food security. Maertens and Swinnen () found that in Senegal, the growth of high‐value agricultural production positively benefited rural women through increased wage income and consequently, reduced gender inequalities in rural areas, especially in large‐scale estate production and agro‐industrial processing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These invasions pose a significant risk in a continent where ~70-80% of the population depends on agriculture for household food security and sustenance [8]. Exports of vegetables from developing countries have immensely increased in the past decades, and horticultural exports have been reported to contribute to improvement in food security and livelihoods in these developing countries [9]. Tomato, Solanum lycopersicum L. (Solanales: Solanaceae) is highly ranked as a food and cash crop [10,11] in Africa and indeed Botswana [12].…”
Section: Introductionmentioning
confidence: 99%
“…They may therefore affect nutrition in positive or also in negative directions. The wider nutritional implications are not yet well understood (15)(16)(17)(18) . Here, I review some of the empirical evidence on linkages between globalising agrifood systems and nutrition.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%